Skeletal muscle atrophy, regeneration, and dysfunction in heart failure: Impact of exercise training - Harrison Gallagher; Paul W. Hendrickse; Marcelo G. Pereira; T. Scott Bowen (Elsevier, 2023)
This review highlights some established and some more contemporary mechanisms responsible for heart failure (HF)-induced skeletal muscle wasting and weakness. We first describe the effects of HF on the relationship between protein synthesis and degradation rates, which determine muscle mass, the involvement of the satellite cells for continual muscle regeneration, and changes in myofiber calcium homeostasis linked to contractile dysfunction. We then highlight key mechanistic effects of both aerobic and resistance exercise training on skeletal muscle in HF and outline its application as a beneficial treatment. Overall, HF causes multiple impairments related to autophagy, anabolic-catabolic signaling, satellite cell proliferation, and calcium homeostasis, which together promote fiber atrophy, contractile dysfunction, and impaired regeneration. Although both wasting and weakness are partly rescued by aerobic and resistance exercise training in HF, the effects of satellite cell dynamics remain poorly explored.